2017
DOI: 10.1371/journal.pone.0177849
|View full text |Cite
|
Sign up to set email alerts
|

Performance in eyeblink conditioning is age and sex dependent

Abstract: A growing body of evidence suggests that the cerebellum is involved in both cognition and language. Abnormal cerebellar development may contribute to neurodevelopmental disorders such as attention deficit hyperactivity disorder (ADHD), autism, fetal alcohol syndrome, dyslexia, and specific language impairment. Performance in eyeblink conditioning, which depends on the cerebellum, can potentially be used to clarify the neural mechanisms underlying the cerebellar dysfunction in disorders like these. However, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
34
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 67 publications
11
34
3
Order By: Relevance
“…We found that eyeblink conditioning was best captured with a bimodal distribution of the learning parameter (see Fig. 2A and Table 2), which is line with a recent study [78]. The main statistical analysis was therefore based on the 'Learner/non-learner model' and the results are presented in Table 3 ('Learner/non-learner model') and Fig.…”
Section: Eyeblink Conditioningsupporting
confidence: 88%
“…We found that eyeblink conditioning was best captured with a bimodal distribution of the learning parameter (see Fig. 2A and Table 2), which is line with a recent study [78]. The main statistical analysis was therefore based on the 'Learner/non-learner model' and the results are presented in Table 3 ('Learner/non-learner model') and Fig.…”
Section: Eyeblink Conditioningsupporting
confidence: 88%
“…Klosterhalfen’s hypothesis fit with Dalla and Shors (2009) , who put forth the hypothesis that there are sex differences in learning, including classical conditioning. A relatively large literature after the Dalla and Shors (2009) article has reported on sex differences in classical conditioning ( Löwgren et al, 2017 ), and some have linked sex differences in learning to sex differences in the stress response ( Merz and Wolf, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Löwgren et al . 69 found that acquisition of conditioned eyeblink responses attains adult levels in humans at the age of 9 years. Similar to eyeblink conditioning, ataxia rating scales show an age-dependency 43 , 44 .…”
Section: Discussionmentioning
confidence: 99%